International business the challenges of globalization - Wild, John J.; Wild, Kenneth L. (Pearson Education, 2014)
Using a cross-functional integrative approach, the authors describe the role played by each business function in international business. They cite numerous examples and cases that deal with non-US companies operating outwith the US.